Evolutionary framework for Lepidoptera model systems - Roe, A.; Weller, S.; Baixeras, J.; Brown, J. W.; Michael P. Cummings; Davis, D. R.; Horak, M.; Kawahara, A. Y.; Mitter, C.; Parr, C. S.; Regier, J. C.; Rubinoff, D.; et al. (Genetics and Molecular Biology of LepidopteraGenetics and Molecular Biology of Lepidoptera, 2010)
“Model systems” are specific organisms upon which detailed studies have been conducted examining a fundamental biological question. If the studies are robust, their results can be extrapolated among an array of organisms that possess features in common with the subject organism. The true power of model systems lies in the ability to extrapolate these details across larger groups of organisms. In order to generalize these results, comparative studies are essential and require that model systems be placed into their evolutionary or phylogenetic context. This chapter examines model systems in the insect order Lepidoptera from the perspective of several different superfamilies. Historically, many species of Lepidoptera have been essential in the development of invaluable model systems in the fields of development biology, genetics, molecular biology, physiology, co-evolution, population dynamics, and ecology.